Novel concepts and nanostructured materials for thermionic-based solar and thermal energy converters. (14th October 2020) - Bellucci, A; Girolami, M; Mastellone, M; Orlando, S; Polini, R; Santagata, A; Serpente, V; Valentini, V; Trucchi, D M
Abstract: Thermal and concentrated solar solid-state converters are devices with no moving parts, corresponding to long lifetimes, limited necessity of maintenance, and scalability. Among the solid-state converters, the thermionic-based devices are attracting an increasing interest in the specific growing sector of energy conversion performed at high-temperature. During the last 10 years, hybrid thermionic-based concepts, conceived to cover operating temperatures up to 2000 °C, have been intensively developed. In this review, the thermionic-thermoelectric, photon-enhanced thermionic emission, thermionic-photovoltaic energy converters are extensively discussed. The design and development processes as well as the tailoring of the properties of nanostructured materials performed by the authors are comprehensively described and compared with the advances achieved by the international scientific community.